Quantitative Methods for the Social Sciences - Stockemer, Daniel (Springer, 2019)
Under what conditions do countries go to war? What is the influence of the 2008–2009 economic crisis on the vote share of radical right-wing parties in Western Europe? What type of people are the most likely to protest and partake in demonstrations? How has the urban squatters’ movement developed in South Africa after apartheid? There is hardly any field in the social sciences that asks as many research questions as political science. Questions scholars are interested in can be specific and reduced to one event (e.g., the development of the urban squatter’s movement in South Africa post-apartheid) or general and systemic such as the occurrence of war and peace. Whether general or specific, what all empirical research questions have in common is the necessity to use adequate research methods to answer them. For example, to effectively evaluate the influence of the economic downturn in 2008–2009 on the radical right-wing success in the elections preceding the crisis, we need data on the radical right-wing vote before and after the crisis, a clearly defined operationalization of the crisis and data on confounding factors such as immigration, crime, and corruption. Through appropriate modeling techniques (i.e., multiple regression analysis on macro-level data), we can then assess the absolute and relative influence of the economic crisis on the radical right-wing vote share.
A Practical Introduction with Examples in SPSS and Stata